Testing Mediators of Reduced Drinking for Veterans in Alcohol Care Management. Issue 9 (26th March 2018) - Moskal, Dezarie; Maisto, Stephen A; Possemato, Kyle; Lynch, Kevin G; Oslin, David W
Abstract: Introduction: Alcohol Care Management (ACM) is a manualized treatment provided by behavioral health providers working in a primary care team aimed at increasing patients' treatment engagement and decreasing their alcohol use. Research has shown that ACM is effective in reducing alcohol consumption; however, the mechanisms of ACM are unknown. Therefore, the purpose of this study is to examine the mechanisms of change in ACM in the context of a randomized clinical trial evaluating the effectiveness of ACM. Materials and Methods: This study performed secondary data analysis of existing data from a larger study that involved a sample of U.S. veterans ( N = 163) who met criteria for current alcohol dependence. Upon enrollment into the study, participants were randomized to receive either ACM or standard care. ACM was delivered in-person or by telephone within the primary care clinic and focused on the use of oral naltrexone and manualized psychosocial support. According to theory, we hypothesized several ACM treatment components that would mediate alcohol consumption outcomes: engagement in addiction treatment, reduced craving, and increased readiness to change. Parallel mediation models were performed by the PROCESS macro Model 4 in SPSS to test study hypotheses. The institutional review boards at each of the participating facilities approved all study procedures before data collection. Results: As hypothesized, results showed that treatment engagement mediated the relation between treatment and both measures of alcohol consumption outcomes, the percentage of alcohol abstinent days, and the percentage of heavy drinking days. Neither craving nor readiness to change mediated the treatment effect on either alcohol consumption outcome. Conclusions: Findings suggest that ACM may be effective in changing drinking patterns partially due to an increase in treatment engagement. Future research may benefit from evaluating the specific factors that underlie increased treatment engagement. The current study provides evidence that alcohol use disorder interventions should aim to increase treatment engagement and reduce barriers to care.